The relationship between student engagement and their perception of success in online learning - Krismiyati Krismiyati; Hanita Yulia (Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
Online learning during the COVID 19  or post pandemic presents challenges not only for the teachers but also the students. Exploring students’ engagement during their online learning is one way of understanding what might contribute to their success although teaching and learning has to be delivered online. This study tries to investigate the correlation between students’ engagement and their perception of their success during their online learning. This study applies quantitative approach in order to answer the hypothesis of this study whether students’ engagement is positively correlated to their perception of success in online learning situation. This study uses questionnaire distributed to 473 students in two vocational schools in Central Java. The statistical descriptive analysis of both variables being measured in this study shows that students are in the medium category of engagement, with one sub variable indicates a high engagement which is their engagement to the material. Apart from the engagement performed by the students, this study has successfully proved that there is positive relationship between students’ engagement and their perception of success. To conclude, this study provides some recommendations to further examine students’ engagement in vocational education.